Kenyan Exports of Nile Perch: The Impact of Food Safety Standards on an Export-Oriented Supply Chain - Henson, Spencer; Mitullah Winnie (World Bank, Washington, D.C., 2013)
Over the past decade, exports of fish and fishery products from developing countries have increased rapidly. However, one of the major challenges facing developing countries in seeking to maintain and expand their share of global markets is stricter food safety requirements in industrialized countries. Kenyan exports of Nile perch to the European Union provide a notable example of efforts to comply with such requirements, overlaid with the necessity to overcome restrictions on trade relating to immediate food safety concerns. Although food safety requirements were evolving in their major markets, most notably the European Union, most Kenyan exporters had made little attempts to upgrade their hygiene standards. Likewise, the legislative framework of food safety controls and facilities at landing sites remained largely unchanged. Both exporters and the Kenyan government were forced to take action when a series of restrictions were applied to exports by the European Union over the period 1997 to 2000. Processors responded by upgrading their hygiene controls, although a number of facilities closed, reflecting significant costs of compliance within the context of excess capacity in the sector. Remaining facilities upgraded their hygiene controls and made efforts to diversify their export base away from the European. Legislation and control mechanisms were also enhanced. Hygiene facilities at landing beaches were improved, but remain the major area of weakness. The Kenyan case illustrates the significant impact that stricter food safety requirements can have on export-oriented supply chains. It also demonstrates how such requirements can exacerbate existing pressures for restructuring and reform, while prevailing supply and capacity issues constrain the manner in which the supply chain is able to respond. In Kenya most of the concerted effort to comply with these requirements was stimulated by the sudden loss of market access in very much a crisis management mode of operation, illustrating the importance of responding to emerging food safety requirements in a proactive and effective manner.